Optimality theory : an overview / edited by Diana Archangeli and D. Terence Langendoen. - Archangeli, Diana B.; Langendoen, D. Terence (Explaining linguistics, 1996)
Containing information on key developments and new research findings this reference work represents the first available survey on optimality theory and its wider applications in the cognitive sciences.